Long-term trends of persistent toxic substances and potential toxicities in sediments along the west coast of South Korea. (February 2020) - Kim, Seonju; Hong, Seongjin; Lee, Junghyun; Kim, Taewoo; Yoon, Seo Joon; Lee, Jongmin; Choi, Kyungsik; Kwon, Bong-Oh; Giesy, John P.; Khim, Jong Seong
Abstract: For decades, in response to industrialization and urbanization, environmental qualities of estuarine and coastal areas of the west coast of Korea have been deteriorating. Long-term changes in concentrations of persistent toxic substances (PTSs) in sediments, including PAHs, styrene oligomers, nonylphenols, and metals and their potential toxicities via AhR- and ER-mediated potencies, and bioluminescent bacterial inhibition, were investigated. Long-term monitoring in five estuarine and coastal areas (2010–2018; 10 sites) showed that concentrations of PAHs and nonylphenols in sediments have declined while concentrations of some metals, Cd, Cr, and Hg have increased. Similarly, AhR-mediated potencies in sediments have declined, but inhibitions of bioluminescent bacteria have increased. Concentrations of sedimentary PAHs and AhR-mediated potencies were significantly ( p < 0.01) and positively correlated. Sources of PAHs from combustion have been gradually declining while inputs from vehicle exhaust by-products have been increasing. Overall, this study brought our attention a balanced regulation in chemical-specific manner. Graphical abstract: Unlabelled Image Highlights: We investigated long-term trends (2010–2018) of PTSs and potential toxicities in sediments. Concentrations of PAHs and nonylphenols in sediments have been declining since 2010. Concentrations of Cd, Cr, and Hg are now increasing in sediments of the west coast of Korea. AhR-mediated potencies have declined, while inhibitions of bioluminescent are increasing. Long-term assessment indicated a balanced environmental regulation for PTSs management.